The Patriarchal Metaphor of Inverted Sexual Reproduction in Milton's Paradise Lost - Tannis, Aivar A. (My University, 1991)
The thesis concerns the question go male writers and their female muses. It explored how and why male writers were able to invert sexual reproduction textually and 'give birth' to their texts. In many aspects, the texts of the seventeenth century represent a resurgence of this patriarchal metaphor. Milton was not immune from patriarchy, and for this reason I have chosen his epic poem, Paradise Lost, as an example of a text very much immersed in this ideology. The first chapter explores the origins of the inverted sexual metaphor in Plato's Symposium and then examines how and why this metaphor influenced the philosophical, theological, and medical texts of seventeenth century England. This chapter employs the critical analysis used by Mary O'brien in her feminist text, The politics of Reproduction. Chapters two and three are close readings of Milton's Paradise Lost, applying the theory discussed in Chapter one. Chapter two explores the relationship between the male characters in Milton's poem who 'give birth' (Satan and Adam) and the women to whom they give birth (Sin and Eve). Chapter three explored the relationship between Milton, his muse, and his text. In the context of the conclusion of these two chapters, Milton affirms the patriarchal belief that God made woman, not as a help to man in the public sphere of knowledge, but as a help to man in the private sphere of reproduction.
[missing pages 33 & 34]
Keywords: English; English Language and Literature; English Language and Literature